Engineered multifunctional Silk fibroin cryogel loaded with exosomes to promote the regeneration of annulus fibrosus. (December 2022) - Wang, Zetao; Luo, Huitong; Zhou, Zhiyu; He, Zhongyuan; Zhu, Shuangli; Li, Dingguo; Gao, Huichang; Cao, Xiaodong
Highlights: AEs/SF cryogel possessed anti-inflammatory, antioxidant stress, cell recruitment, and regulating fibrocartilage differentiation abilities. AEs/SF cryogel can effectively seal AF defect and promote the regeneration of AF defects. AEs/SF cryogel regulate the IVD immune microenvironment by promoting the polarization of macrophages from M1 to M2 phenotype and reduce oxidative stress. Abstract: Annulus fibrosus (AF) defect is a common clinical problem caused by lumbar disc herniation. Many AF mechanical closure devices have been developed to prevent recurrent herniation after discectomy. However, the high-inflammatory and high-ROS environment caused by AF defects make it difficult for mechanical devices to effectively reverse the degenerative process and promote regeneration of AF defects. Based on this, in this study, a multifunctional silk fibroin (SF) cryogel scaffold loaded with annulus fibrosus cell-derived exosomes (AEs) was constructed to inhibit intervertebral disc degeneration and promote regeneration of defects by regulating the immune microenvironment and scavenging ROS. SF cryogel has a uniform macroporous structure and good shape memory function, which could effectively seal AF and achieve the sustained release of AEs. In vitro cell experiments showed that AEs/SF cryogel possessed anti-inflammatory, antioxidant stress, cell recruitment, and regulating fibrocartilage differentiation abilities. In vivo animal experiments also further confirmed that AEs/SF cryogel could effectively seal AF defect of the rat caudal vertebra after acupuncture and regulate the IVD immune microenvironment by promoting the polarization of macrophages from M1 to M2 phenotype and reduce oxidative stress, which contributed to reversing the degeneration process and promote the regeneration of AF defects, indicating a potential application for AF defect repair. Graphical abstract: The AEs/SF cryogel could effectively seal AF and promote its regeneration by regulating the IVD microenvironment. Image, graphical abstract